Electronic Government Procurement : Readiness Self Assessment - Asian Development Bank; Inter-American Development Bank; World Bank (World Bank, Washington, DC, 2014)
This Electronic Government Procurement (e-GP) Readiness Assessment (Assessment) is intended to assist a jurisdiction to conduct a high level review of its procurement environment to determine its level of readiness to make a transition to e-GP in a sustainable manner. It will assist a jurisdiction to determine the degree to which the components and their subcomponents, which underlay e-GP, are in place. Conducting a current assessment is usually one of the key initial steps for developing an implementation plan for e-GP. The assessment addresses the strategic foundations of e-GP by examining the components that are the basis for planning the transition to e-GP. The components underlying e-GP are those issues which, when addressed and integrated, provide a jurisdiction with a framework for an effective, efficient and sustainable approach to e-GP. They have been developed both from research of and experience with a range of existing procurement environments in different countries. Additionally, the assessment invites comment from respondents on other factors seen as influencing readiness, and on the critical changes required to implement e-GP. These comments are grouped under the heading respondent views.